2017
DOI: 10.1111/jfd.12655
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the occurrence of infectious myonecrosis virus in pond‐reared Litopenaeus vannamei (Boone, 1931) in India

Abstract: Whiteleg shrimp, Litopenaeus vannamei, with clinical sign of muscle opaqueness with reddish colour at the distal abdominal segments were observed in farms located in West Bengal State, India. The mortality of shrimp in all disease outbreak ponds ranged from 20% to 50%, and mortality increased gradually. The RT-PCR assay of these samples using primer sets specific to infectious myonecrosis virus (IMNV) revealed its presence in the disease outbreak ponds. The IMNV infection was reproduced in healthy shrimp by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…The introduction of exotic species has the risk of disease outbreaks caused by the pathogens which are not reported previously in India. Recently, the occurrence of Enterocytozoon hepatopenaei and IMNV has been reported after the introduction of L. vannamei to Indian aquaculture system (Rajendran et al, ; Sahul Hameed et al, ; Santhoshkumar et al, ). Behera et al () reported for the first time the occurrence of TiLV in Nile tilapia farms in India.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of exotic species has the risk of disease outbreaks caused by the pathogens which are not reported previously in India. Recently, the occurrence of Enterocytozoon hepatopenaei and IMNV has been reported after the introduction of L. vannamei to Indian aquaculture system (Rajendran et al, ; Sahul Hameed et al, ; Santhoshkumar et al, ). Behera et al () reported for the first time the occurrence of TiLV in Nile tilapia farms in India.…”
Section: Discussionmentioning
confidence: 99%
“…A surveillance program supported by National Fisheries Development Board of ICAR, India is being carried out to monitor aquaculture systems throughout the country for emerging diseases in shrimp, prawn and fish. As a result of this program which is now into its third year, the occurrence of Enterocytozoon hepatopenaei (2, 3) and infectious myonecrosis virus (IMNV) in pond-reared L. vannamei (4), cyprinid herpesvirus-2 in goldfish (5) and tilapia lake virus in Nile tilapia (6) has been reported. In the field condition, various control strategies such as improvement of environmental conditions, stocking of specific pathogen-free shrimp post-larvae and augmentation of disease resistance by oral immunostimulants, are being applied to control WSSV infection.…”
Section: Introductionmentioning
confidence: 99%
“…The production of L. vannamei reached almost 5 lakh tonne in 2017. As expected, the culture of L. vannamei was found to be successful in the beginning but is now facing difficulties because of serious disease problems caused by EHP, IMNV and WSSV (Rajendran et al, ; Sahul Hameed et al, ; Santhoshkumar et al, ). Recently, a new strain of WSSV with a deletion of 13,170 bp at five positions in the genome of WSSV relative to WSSV‐TH was reported after the introduction of L. vannamei into Indian waters (Sivakumar et al, ).…”
Section: Discussionmentioning
confidence: 80%